Inheritance in same-sex communities in the Republic of Serbia - Račić Anđelka (Megatrend Revija)
Social communities are prone to evolutionary changes that are initiated sometimes by the dominant minority, and sometimes under the influence of the quantitative energy of the oppressed minority. Partnerships have been prone to change for centuries. From the traditional patriarchal family, through the recognition of the rights of extramarital unions, and the acceptance of same-sex civil unions, in order to promote samesex marriage in the last decade. The paper deals with the review of the development and implementation of the idea of recognizing the right to marriage for same-sex couples, the global attitude towards the same with special reference to the Republic of Serbia. Namely, the Republic of Serbia does not recognize same-sex marriages, nor does it recognize them by law, no matter where they were concluded, and in this sense, the paper explains the possibilities of inheritance between same-sex partners, regardless of the fact that legal inheritance is impossible.